AN An Analysis of Students’ Ability in using Suffixes by using Online Media Quizlet at Grade X of SMAN 2 Sungai Penuh - Dwirati, Elsi; Ihsan, Rodiyal; Ningsih, Darda Sutfi (Indo-MathEdu Intellectuals Journal, 2023)
This research is aimed to describe the students’ ability in using derivational suffixes. The research focuses on analyzing the students’ ability in using four types of derivational suffixes by online media Quizlet. The design of the research is quantitative descriptive approach. The population of the research is 342 students and assigned 32 students grade X of SMAN Sungai Penuh academic year of 2023/2024 as the sample. The data collected by using Quizlet and analyzed by calculating the total score, the percentage, and the average of students’ ability. Then, calculating the mean score to determine the students’ ability in using suffixes. The researcher found out the percentage students’ ability in using suffixes. 19.35% students included in excellent level. 35.48% students included in good level. 38.71% students included in fair level, 6.45% students included in poor level and 0% included in very poor level. The researcher also found the students’ average ability in using each type of suffixes. In nominal suffixes 58.06 or good level. In verbal suffixes, 66.45 or good level. In adjectival suffixes 69.68 or good level. In adverbial suffixes 67.74 or good level. According to the total mean score 65.16, the researcher categorized the Students’ Ability in Using Suffixes by using online media quizlet at grade X of SMAN 2 Sungai Penuh was good ability or high ability